Satellite-Earth Integration Intelligent Resource Management and Control Architecture of Giant Sensing Constellation - Yingte CHAI; Gang WANG; Chao ZHANG; Guangxi ZHU; Wei FU; Zhengqiang GUO (天地一体化信息网络)
The giant sensing constellation will have the capabilities of on-board automatic processing, on-board independent planning, multisensors and multi-mode automatic switching.The traditional control mode of relying solely on the ground system can no longer meet the requirements of the giant sensing constellation.According to the requirements of intelligent and networked control, an integrated intelligent resource management and control architecture was proposed.It was based on the integration of satellite and earth.The work contents of satellite and earth were specifically designed.The interaction mechanism between satellite and earth was designed.The architecture it proposed could be well applied to the independent resource management and controlled of giant sensing constellation.The architecture realized the ＆quot;networking, autonomy and intelligence＆quot; of the giant sensing constellation and it could played an important role in major national security emergency response and other tasks.